Effective Use of Ferric Sulphate and Ferric Chloride in Treatment of Dairy Industry Wastewater - M. Dabhi, Yogesh; A. Parmar, Kokila (Asian Journal of Chemistry, 2010)
Dairy plants need usually large quantities of clean water. More than 90 % of clean water is converted into wastewater demonstrating very high potential risk of environmental pollution. The present study is undertaken to investigate, under the same analytical conditions, the efficiency of ferric sulfate and ferric chloride used as coagulant in chemical treatment of raw wastewater collected from dairy plant. Results of visual and physicochemical evaluation of chemically treated wastewater indicated significant improvement of their selected characteristics, however different response to the coagulant treatment was observed within the tested samples. Removal efficiencies for individual parameters varied in the wide range between 20.9 and 97.2 %.